Evaluation of heterogeneous quaternary ammonium catalyst for transesterification of trigycerides - Wan Mohd Hafizuddin, Wan Yussof (2012)
Biodiesel is a mixture of an alkyl ester of long chain fatty acids produced by transesterification of triglycerides with lower alcohols such as methanol, in the presence of acid or base catalysts. Nearly all biodiesel processes use mogeneous base catalysts that cannot be recovered and necessitate neutralisation of the glycerol-rich phase (a byproduct of the reaction). This increases the number of downstream separation steps, thereby increasing the capital cost of biodiesel production processes. Replacing liquid homogeneous catalysts with solid heterogeneous catalysts can intensify the process, by reducing the total number of process steps, eliminate or reduce waste streams and result in lower production costs, as the catalyst will not have to be continually replaced.Strong anion exchange resins with QNOH, have the potential to be developed and employed as heterogeneous catalyst for transesterification, as they are chemically stable to leaching of the functional group. In this present work, nine different synthesized anion exchange resins (SIER1-9) were prepared by suspension polymerization of vinylbenzyl chloride-divinylbenzene (VBC-DVB) copolymers in the presence of nheptane as a pore-forming agent. These SIERs were evaluated as catalysts for transesterification of triacetin. It was found that the "SIER-6" catalyst prepared with the highest dilution degree (200%) and the lowest DVB content (10% DVB), achieved the highest triacetin conversion (95.6% after 4h). This catalyst had the highest true pore volume (0.89 cm 3 /g) and surface area (398.8 m 2 /g). In contrast, the "SIER-7" catalyst synthesized with the lowest dilution degree (50%), but highest DVB content 40%),resulted in the lowest triacetin conversion at 64.3%. Although there is a siderable improvement in the physicochemical properties of the IERs, such as surface area, 'true pore' volume and diameter, transesterification using rapeseed oil was rather poor with only 16 wt. % of FAME obtained over SIER-6 after 6h reaction.